On approximation of homomorphisms of algebras of entire functions on Banach spaces - Pryimak, H.M. (Carpathian Mathematical Publications, 2019)
It is known due to R. Aron, B. Cole and T. Gamelin that every complex homomorphism of the algebra of entire functions of bounded type on a Banach space X can be approximated in some sense by a net of point valued homomorphism. In this paper we consider the question about a generalization of this result for the case of homomorphisms to any commutative Banach algebra A. We obtained some positive results if A is the algebra of uniformly continuous analytic functions on the unit ball of X.